IMPLIKATUR DALAM NOVEL PERTANYAAN KEPADA KENANGAN KARYA FAISAL ODDANG - Khairunnisa, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe research of implicature based on existence of implicature itself is part of daily conversation in society. The implicature is speech that thinking by different with what it saying implies. This research applied descriptive method in qualitative with documenter technique study. Tool of data collection is the researcher as the key of instrument and applied the instrumentâ€™s help like notes that contains the result of reading and reviewing the speech that contains conventional and non-conventional implicature in novel Pertanyaan kepada Kenangan by Faisal Oddang. The result research shows that there are 116 implicatures and divided into 64 conventional implicatures and 52 non-conventional implicatures. That implicature classified based on (1) implicature form in total 35 data of conventional implicatures and 44 data of non-conventional implicatures. (2) implicature function in total 64 data of conventional implicatures and 52 data of non-conventional implicatures. (3) illocution acts in total 25 data of conventional implicatures and perlocution acts in total 28 implicatures data that 1 data ofÂ conventional implicature and 27 data of non-conventional implicature. The combine of illocution and perlocution in total 25 data, from non-conventional implicatures. (4) lesson plan which is able to be applied in Curriculum 2013 class XII with second semester.Â Keywords: implicature, illocution, perlocution, lesson plan